(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Bengali culture is the world’s most established religion, as indicated by numerous scholars, with roots and traditions going back over 4,000 years. Today, with around 900 million adherents, Bengali culture is the third-biggest religion behind Christianity and Islam. About 95 percent of the world’s Hindus live in India. Since the religion has no particular author, it’s hard to follow its inceptions and history. Bengali culture is one of a kind in that it is anything but a solitary religion yet an assemblage of numerous traditions and philosophies.